Prototipo web para el cálculo de energía solar fotovoltaica en la ciudad de Loja mediante el uso del modelamiento matemático - Ureña Hernández, Johanna Elizabeth (2024)
The use of renewable energy sources, such as photovoltaic systems (PVS), is essential to improve the quality of life now and in the future. However, the challenges in making decisions about their installation are a significant limitation, related to location, energy benefits and economics. Therefore, research and development of web applications that facilitate this decision making is essential. This research focuses on the development of a web prototype for decision making regarding the installation of PVS, with the purpose of facilitating the adoption of renewable energy sources. The system was developed using the XP methodology, efficiently organizing the activities in the planning, design, coding and testing phases. During these phases, structured interviews and surveys were used to collect information relevant to the research. Likewise, the 4+1 architectural model allowed defining the three-layer client-server architecture. Quantitative mathematical modeling helped in performing simulations to verify the viability of these systems. The simulation results allowed a comparison of electricity consumption and monthly bills before and after the installation of a PV system. Finally, the system was evaluated through acceptance tests and the application of the TAM methodology to determine its degree of acceptance. In this way, it was determined that the acceptance of the prototype by users is "High" according to the quality criteria, with a weighted average of 4.4 and 83% of respondents answering "Agree" or "Strongly agree". This indicates that the prototype has a high degree of acceptance, as it is perceived as useful and easy to use, which reinforces its potential for implementation, since it helps in decision making by providing a reliable tool to evaluate the impact of these systems. Key words: IEEE 830, solar irradiation, XP Methodology, photovoltaic systems, TAM Methodology